Solid State Physicochemical Properties and Applications of Organic and Metallo- Organic Fullerene Derivatives - Mitsari, Efstratia; Romanini, Michela; Zachariah, Manesh; Macovez, Roberto (Current Organic Chemistry, 2016)
We review the fundamental properties and main applications of organic derivatives and complexes of fullerenes in the solid-state form. We address in particular the structural properties, in terms of crystal structure, polymorphism, orientational transitions and morphology, and the electronic structure and derived properties, such as chemical activity, electrical conduction mechanisms, optical properties, heat conduction and magnetism. The last two sections of the review focus on the solid-state optoelectronic and electrochemical applications of fullerene derivatives, which range from photovoltaic cells to field-effect transistors and photodetectors on one hand, to electron- beam resists, electrolytes and energy storage on the other.
Keywords: Crystal structure